2008
DOI: 10.1097/mcg.0b013e318046ea86
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Celiac Disease in Mexican Mestizo Adults With Type 1 Diabetes Mellitus

Abstract: As in other populations, we demonstrated a high prevalence of biopsy-proven CD (5.9%) among Mexican Mestizo patients with type-1 diabetes. Clinicians should be aware of this common association in this ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…It is foreseeable that the autoantibodies generated against the neo-epitope may represent the best means for screening populations, diagnosing high-risk groups and identify silent or latent patients. In fact, several studies have shown the superiority of screening for CD using the neo-tTg/DGPs complex strategy in the general population [26,27] or in high-risk groups' subjects [16,18,19,[28][29][30]. The present results go along this serological diagnostic strategy and add the aspect of intestinal damage reflection.…”
Section: Discussionmentioning
confidence: 77%
“…It is foreseeable that the autoantibodies generated against the neo-epitope may represent the best means for screening populations, diagnosing high-risk groups and identify silent or latent patients. In fact, several studies have shown the superiority of screening for CD using the neo-tTg/DGPs complex strategy in the general population [26,27] or in high-risk groups' subjects [16,18,19,[28][29][30]. The present results go along this serological diagnostic strategy and add the aspect of intestinal damage reflection.…”
Section: Discussionmentioning
confidence: 77%
“…[44][45][46] Including patients with serology and increased IELs without atrophy and 2 previously treated patients, the prevalence approaches 2%. The high prevalence of celiac disease in this population likely is the result of the carriage of the at risk genotype that is common in Finnish and Swedish populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is foreseeable that the autoantibodies generated against the neo-epitope complex may represent the best means for screening populations and for diagnosing high-risk groups for identification of the silent or latent patients. In fact, several studies have shown the superiority of screening for CD using the tTG/DGPs complex strategy in the general population [29,30] or in groups of at-risk subjects [17,18,19,31,32,33]. Most recently, neo-epitope DGP/tTG autoantibodies were shown to present a new and sensitive serological marker of dermatitis herpetiformis, a disease closely related to CD [34].…”
Section: Diagnostic Autoantibodies In CDmentioning
confidence: 99%